MRI evaluation of solid soft tissue masses of the fingers with pathology correlation. Issue 135 (February 2021) - Serhal, Ali; Samet, Jonathan; Shah, Chirag; Omar, Imran; Youngner, Jonathan
Highlights: Most solid masses of the fingers are benign, giant cell tumor of the tendon sheath is the most common tumor. Magnetic resonance imaging can be helpful in narrowing the differential diagnosis of the solid finger lesions. Magnetic resonance imaging provides the surgeon with crucial information prior to surgical planning. Abstract: Objective: Space occupying lesions of the fingers are commonly encountered in clinical and radiology practice. The objective of this study was to determine the characteristics of these lesions on MRI and to correlate with surgical pathology results. Material and methods: This IRB-approved HIPAA-compliant study retrospectively evaluated the clinical, imaging and pathology findings of 100 consecutive patients referred for evaluation of solid soft tissue masses of the fingers. Only solid lesions with MR imaging prior to surgery were included in this study. MR images and when available corresponding radiographs were evaluated by two radiologist in regard to signal characteristics, relation to surrounding structures and enhancement. All masses were classified into different groups based on pathology results. Results: Tenosynovial giant cell tumor (TSGCT) and fibroma of the tendon sheath were the most common solid tumors (36 %) and malignant tumors represent only 5% of the cohort. 70 % of masses with low T2 signal were TSGCT and fibroma of tendon sheath; 100 % of masses with peripheral high T2 signal and central low T2 signal/thrombus were vascular lesions, representing 41 % of the total vascular lesions in the cohort. Additionally, 100 % of serpiginous/tubular shaped masses were vascular lesions and 67 % of masses with infiltrative borders were malignant masses. Enhancement was important in identifying solid lesions but there was no statistical difference between groups related to enhancement pattern. There was a good agreement for all analyses between both readers. Conclusion: Typical MR findings can help to narrow the differential diagnosis in the evaluation of finger masses and provide crucial information to guide further management.